Fracture healing: cellular mechanisms and impact of parathyroid hormone and its analogs - Bikle, Daniel (Frontiers in Endocrinology, 2025)
Fractures engender a multimillion dollar medical cost to society with substantial morbidity and mortality for the patients. In long bones fracture repair takes place at 3 distinct sites: intramembranous bone formation along the outer surface of the periosteum, endochondral bone formation bridging the fracture site, and intramedullary bone formation within the marrow at the ends of the fractured bone. Fracture repair occurs in 4 overlapping phases. 1. Hematoma formation and a proinflammatory response that activates the stem cells, 2. initiation of chondrogenesis, osteogenesis, and angiogenesis, 3. mineralization of the soft callus to form the hard callus, 4. remodeling of the callus to regenerate an intact bone. Stem cells in the periosteum, marrow, and overlying muscle supply the cells for the repair process. Parathyroid hormone (PTH) in its 1–34 form (teriparatide) and its analog abaloparatide are promising drugs to promote fracture repair. PTH acts via its receptor (PTHR) which is expressed in essentially all skeletal cells involved in fracture repair. Its anabolic actions are mediated by a number of interacting pathways including cAMP/PKA, Wnt, BMP, IGF1 and the bidirectional signaling of Ephrin B2/Eph B4. Progress in this field will lead to better treatment of fractures especially those slow or fail to heal.